Applications of self-organising multi-agent systems - Bernon, Carole (Informatica (Ljubljana), 2006)
A lot of work is devoted to formalizing and devising architectures for agents'cooperative behaviour, for coordinating the behaviour of individual agents within groups, as well as to designing agent societies using social laws. However, providing agents with abilities to automatically devise societies so as to form coherent emergent groups that coordinate their behaviour via social laws, is highly challenging. These systems are called self-organised. We are beginning to understand some of the ways in which self-organised agent systems can be devised. In this perspective, this paper provides deveral examples of multi-agent systems in which self-organisation, based on different mechanisms, is used to solve complex problems. Several criteria for comparison of self-organisation between the different applications are provided.
Keywords: večagentni sistem; samoorganizacija; programska oprema